Evolution of reduction process from tungsten oxide to ultrafine tungsten powder via hydrogen - Wang Yue (De Gruyter, 2021)
Herein, the evolution of reduction process of ultrafine tungsten powder in industrial conditions was investigated. The transition process of morphology and composition was examined via SEM, XRD, and calcination experiments. The results show that the reduction sequence of WO2.9 was WO2.9 → WO2.72 → WO2 → W on the surface, but WO2.9 → WO2 → W inside the oxide particles. With the aid of chemical vapor transport of WOx(OH)y, surface morphology transformed into rod-like, star-shaped cracking, floret, irregularly fibrous structure, and finally, spherical tungsten particles.